Doença periodontal como fator de risco coronariano - Accarini, Renata (2006)
Positive association between periodontal disease and coronary diseases is unclear concerning physiopathologic mechanisms and causal relationship. The aim of this study was to assess the association between active periodontal disease active and obstructive coronary artery disease in patients with acute coronary syndromes. Method: 361 (57.3% males; mean age 60.5+12.2) patients referred for diagnostic coronary vessel disease were assessed for periodontal disease and also submitted to coronary angiography with diagnostic and prognostic purposes. Each patient underwent a full-mouth periodontal examination which included gingival bleeding, plaque index, periodontal pocket depths, attachment levels and missing teeth. For statistical analysis was used the Exact Fisher test and was accepted an Alfa error of 5%. Results: 28% patients haven t significant coronary vessel obstructions (<50% diameter obstruction) and 72.0% had significant obstructive disease (>50% diameter obstruction). The Exact Fisher Test showed p-value of 0.0245 and ODDS Ratio of 2.571 (95%CI from 1.192 to 5.547). So there was a 2.5 fold increase in the chance for active periodontal disease in patients with significant obstructive coronary artery disease. Conclusion: Our study indicates a positive and significant association between periodontal disease and obstructive coronary disease among patients with acute coronary syndromes becoming periodontal disease as a potential risk factor in etiology and outcome of atherosclerotic plaque. Results of this and other investigations should be taken into account in the future researches in order to validate this association.